2020
DOI: 10.26848/rbgf.v13.5.p2103-2113
|View full text |Cite
|
Sign up to set email alerts
|

Fitossociologia de manguezais em zonas urbanas: um estudo de caso em Aracaju, Sergipe

Abstract: O objetivo deste estudo foi comparar a composição florística e a estrutura fitossociológica dos bosques de manguezais de áreas urbanas em Aracaju, estado de Sergipe, com diferentes tempos de regeneração e intensidades de impacto antrópico. Para o levantamento fitossociológico, foi adotado o método de parcelas múltiplas, sendo seis ou sete parcelas distribuídas equitativamente em dois transectos paralelos em quatro bosques de manguezais nos bairros 13 de julho, Porto Dantas, São Conrado e Mosqueiro. Destes, som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(14 reference statements)
0
2
0
3
Order By: Relevance
“…The present study reported a total of 14 (3.7%) dogs positive for Diro laria immitis micro lariae. The worldwide prevalence of D. immitis infections in dogs is 10.91%, while in Brazil, canine infections have been reported in most states, with prevalence rates over the last decade ranging from 2.1% in Florianopolis, south of Brazil, to 62.2% in Rio de Janeiro, the state with the higher annual prevalences Even though the city of Aracaju has an adequate climate for mosquitoes development, and many environments favorable for the vector and disease spread (mangroves, beaches, forests) in close contact with the urban environment, the low prevalence of canine D. immitis infections observed (3.7%) can be explained by the chosen diagnostic technique (Santana et al, 2020). Many studies have reported that serological and PCR-based methods demonstrated a higher e ciency on the diagnostic of blood larial diseases, due to their higher sensitivity and speci city, in comparison to Knott's technique and other microscopic parasitological techniques (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study reported a total of 14 (3.7%) dogs positive for Diro laria immitis micro lariae. The worldwide prevalence of D. immitis infections in dogs is 10.91%, while in Brazil, canine infections have been reported in most states, with prevalence rates over the last decade ranging from 2.1% in Florianopolis, south of Brazil, to 62.2% in Rio de Janeiro, the state with the higher annual prevalences Even though the city of Aracaju has an adequate climate for mosquitoes development, and many environments favorable for the vector and disease spread (mangroves, beaches, forests) in close contact with the urban environment, the low prevalence of canine D. immitis infections observed (3.7%) can be explained by the chosen diagnostic technique (Santana et al, 2020). Many studies have reported that serological and PCR-based methods demonstrated a higher e ciency on the diagnostic of blood larial diseases, due to their higher sensitivity and speci city, in comparison to Knott's technique and other microscopic parasitological techniques (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the prevalence of D. immitis infections ranges from 1 to 45% in over 12 of the total 26 states (Bendas et al, 2017). The city of Aracaju, capital of the state of Sergipe, northeastern region of Brazil, is a coastal city with a characteristic tropical climate (high temperatures and humidity) and the presence of many natural areas (mangroves, forests, and beaches) in close contact with the urban environment (Anjos et al, 2017;Santana et al, 2020). The city has about 672 thousand inhabitants and an estimated canine population of 45 thousand animals, of which approximately 10% are stray (IBGE, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com Santana et al (2020) a microbacia do Rio Poxim possui "manguezal bem desenvolvido, mas os canais existentes servem como receptores finais de grande parte de esgotamento doméstico da região, assim como os despejos de resíduos sólidos sobre o rio Poxim.…”
Section: áRea De Estudounclassified
“…A fitossociologia compreende a busca das causas e efeitos da coabitação florística em determinado ambiente, a partir da descrição da comunidade vegetal e de seus padrões comuns em escala geográfica (Santana et al, 2020;Gama et al, 2018). É uma ferramenta para o estudo das interrelações de espécies vegetais que formam uma comunidade, além de ser indicadora eficiente para impulsionar os conhecimentos ecológicos dos ambientes, avaliar e monitorar a vegetação (Bianchin e Bellé, 2013;Oliva et al, 2018).…”
Section: Introductionunclassified